THE SYNERGY BETWEEN GOVERNMENT AND CIVIL SOCIETY ORGANIZATIONS TO IMPROVE COMMUNITY WELFARE - rosana, yenni (JURNAL LITERARY CRITICISM, 2019)
The government plays an important role in guaranteeing the success of a country.  Similarly, for a province; the government of a province should take actions to improve the capacity of the province. However, when the government cannot synergize its role with the mandate of civil society organizations, the community will be living in an ambiguous situation. Civil society organizations can act against the government. Meanwhile, there could be some of the community will choose to be in the civil society organizations? side, or in the government?s side. This essay will describe how the Aceh Province in Indonesia has experienced various changes in the lives of its people because there was no synergistic opinion between the government and certain civil society organizations. Meanwhile, community welfare is the main goal to be achieved, so it is necessary to have good cooperation between government and civil society organizations. Although civil society organizations will act as oppositions or partners, it should aim for the better life of the community.   Keywords: Government, Civil Society Organizations, Community welfare